Gambaran Self-Care Pasien dengan Penyakit Jantung Koroner Pasca Kateterisasi Jantung - Arianca, I Nyoman; Intan Saraswati, Ni Luh Gede; Satya Laksmi, I Gusti Ayu Putu; Yuni Lestari, Ni Kadek (Jurnal Gema Keperawatan, 2024)
Coronary heart disease is one of the most common cardiovascular diseases throughout the world which results in high rates of mortality, morbidity and also has a financial impact. One of the main management for coronary heart disease patients is self-care. Several studies show that treatment outcomes for coronary heart patients are better in patients who engage in consistent self-care. Programs and guidelines regarding self-care for coronary heart patients have been proven to reduce rehospitalization rates. The results of other research show there is a link between a good quality of life and good self-care. The aim of this research is to determine the description of self-care for coronary heart patients after catheterization at the Integrated Heart Care Installation at Prof.Dr.I.G.N.G Ngoerah Hospital. This research uses a descriptive analytical design with a cross sectional approach using the SC-CHDI questionnaire. The total sample was 219 respondents using purposive sampling technique. The results of the study showed that 77,2% respondent have sufficient catagory, Self-Maintenance results for coronary heart patients at the Integrated Heart Care Installation at Prof. Dr. I. G. as many as 119 people (54,3%). Self-care-confidence was in the sufficient category, 195 respondents (89%) and the results of self-care management for coronary heart patients were in the sufficient category,115 respondents (52,5%). The description of self-care for coronary heart disease sufferers is influenced by respondent characteristics such as age, gender, education, occupation, and length of illness.